Short notes on a recent volume regarding patronage in Macedonian Byzantium (867-1025) (Bisanzio e l'Occidente, 2018)
Short notes around a recent study on patronage in the age of the Macedonian dinasty (867-1025). Architecture, frescoes and mosaics, luxury arts, illuminated manuscripts from an age of splendour studied with the closest attention to the monument itself, to the sources and secondary literature. An understudied field of Byzatine art comes to life anew.